Akibat Hukum Pembatalan Perkawinan terhadap Hak-Hak Anak yang Lahir Sebelum Perkawinan Dibatalkan: Analisis Kasus Jessica Iskandar dan Ludwig Franz Willibald - Citranti Hanifah Dewani; Farsya Dalila Alamsyah; Ilaria Sekar Ailsa; Leon L (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Marriage annulment is a legal remedy that declares a marriage to be legally flawed from the outset. This study examines the judge's legal considerations in Decision Number 586/Pdt.G/2014/PN.Jkt.Sel regarding the annulment of the marriage between Jessica Iskandar and Ludwig Franz Willibald, as well as its legal consequences for the rights of children born from the marriage. The method used is normative legal research with a case approach and a statute approach. The results of the study indicate that the judge granted the annulment of the marriage because the marriage documents were proven to be invalid, including a certificate of blessing that was not recognized by the True Jesus Church and the identity of the pastor who could not be verified. However, based on Article 28 paragraph (2) letter a of Law Number 1 of 1974 concerning Marriage, the annulment decision does not apply retroactively to children. Children born from an annulled marriage remain legitimate children, have a civil relationship with both parents, and are entitled to support, care, education, and inheritance. This research confirms that the principle of the best interests of the child must always be prioritized in all marriage annulment cases.